A contribution to the implicit / explicit debate on grammar learning: the case of contrast connectors - Costa, Ana Luísa (2022)
In this paper, studies on language acquisition and development are seen as most relevant to grammar teaching and learning. Grammar teaching may be conceived as a process of building awareness of the language used from the earliest stages, as well as a process of scaffolding knowledge depending on later language development. In this perspective, grammar instruction (including curricular orientations) must take into account what belongs to spontaneous linguistic knowledge, and which linguistic knowledge crucially depends on the richness of discourse experiences at school. Data on the acquisition of contrast connectives in European Portuguese will support the idea that, even assuming that some innate principles rule early language acquisition, linguistic proficiency depends on language learning experiences accumulated through years of schooling. Furthermore, language development is not entirely accomplished by linguistic mastery: the ability to explain language through language may be considered a later stage of linguistic accuracy, associated with formal instruction.